Shiyeyi Language Planning in Botswana: International Connections and Local Imperatives. Issue 3 (4th May 2019) - Nyati-Saleshando, Lydia
ABSTRACT: Shiyeyi is one of the 28 languages spoken in Botswana. It is an endangered language because it is no longer being passed on to the children. This article describes micro language planning efforts to revive Shiyeyi over a period of 17 years. The classical and critical approaches to language planning are applied to this case to highlight the interplay between power relations, social exclusion, and social change. The overall planning context is provided and the achievements are outlined as evidence of social change in three areas. The challenges are outlined as evidence of power relations stemming from historical and socio-political exclusion, thus affecting the identity of the Wayeyi. It is argued that the project was a search for cultural identity, social inclusion and economic advancement. Further, it is the holistic approach to rights advocacy at the micro planning level that brought about change, giving hope for the revival of Shiyeyi.